2021
DOI: 10.1139/cjfr-2020-0459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil nutrients and stand structure on aboveground net primary productivity of oak secondary forests in the forest–steppe transition zone of Loess Plateau, China

Abstract: Liaodong oak (Quercus liaotungensis) dominated forests contribute to the few natural forest ecosystems in the semiarid Loess Plateau region in China. This study investigated the influence of soil nutrients and stand structure on aboveground net primary productivity (ANPP) in the oak communities. We aimed to understand the major factors and their possible pathways that determine the ecosystem productivity. The biomass and ANPP were estimated using plot surveys and litterfall collection in fixed plots. Linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…A relationship between soil type and SI was also reported by Bijak & Sacewicz (2018). A study on the impact of environmental factors on site productivity in southern Poland (Tymińska-Czabańska et al, 2021) and the influence of soil characteristics on oak secondary forests in China (Sun et al, 2021) also demonstrated the relationship between soil and geology with site productivity.…”
Section: Discussionmentioning
confidence: 96%
“…A relationship between soil type and SI was also reported by Bijak & Sacewicz (2018). A study on the impact of environmental factors on site productivity in southern Poland (Tymińska-Czabańska et al, 2021) and the influence of soil characteristics on oak secondary forests in China (Sun et al, 2021) also demonstrated the relationship between soil and geology with site productivity.…”
Section: Discussionmentioning
confidence: 96%